1999
DOI: 10.1021/bi991983j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steric Bulk and Electrostatics on the Hydroxylation Regiospecificity of Tryptophan Hydroxylase:  Characterization of Methyltryptophans and Azatryptophans as Substrates

Abstract: Tryptophan hydroxylase is a pterin-dependent amino acid hydroxylase that catalyzes the incorporation of one atom of molecular oxygen into tryptophan to form 5-hydroxytryptophan. The substrate specificity and hydroxylation regiospecificity of tryptophan hydroxylase have been investigated using tryptophan analogues that have methyl substituents or nitrogens incorporated into the indole ring. The products of the reactions show that the regiospecificity of tryptophan hydroxylase is stringent. Hydroxylation does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…1 kcal mol -1 lower than the overall effective energy barrier for the formation of the Fe IV =O species (13.9 kcal mol -1 ). These calculated barrier heights are in excellent agreement with the fact that, in most cases, formation of the hydroxylating intermediate appears to represent the rate-limiting step, although there are also examples where oxygen insertion into the amino acid substrate takes on a partial or complete rate-determining role, [3,27] indicating that the two barriers are intrinsically of comparable magnitudes and that their relative order may be modified by the exact choice of enzyme, substrate, and cofactor.…”
Section: Rebinding Of Water Moleculessupporting
confidence: 68%
See 1 more Smart Citation
“…1 kcal mol -1 lower than the overall effective energy barrier for the formation of the Fe IV =O species (13.9 kcal mol -1 ). These calculated barrier heights are in excellent agreement with the fact that, in most cases, formation of the hydroxylating intermediate appears to represent the rate-limiting step, although there are also examples where oxygen insertion into the amino acid substrate takes on a partial or complete rate-determining role, [3,27] indicating that the two barriers are intrinsically of comparable magnitudes and that their relative order may be modified by the exact choice of enzyme, substrate, and cofactor.…”
Section: Rebinding Of Water Moleculessupporting
confidence: 68%
“…[25] It has subsequently also been reported that the second main step, the hydroxylation of the aromatic substrate (see below), more specifically the incorporation of the oxygen into the substrate, could, completely or partially, be rate-limiting. [26,27] In the second main reaction step, the aromatic amino acid substrate is hydroxylated by Fe IV =O through an attack by the carbon atom in the aromatic ring on the oxygen atom in Fe IV =O, followed by a subsequent 1,2-hydride transfer, a so-called NIH shift, to form a dienone. [28][29][30] Organic catalysts are not able to perform NIH shifts, and even the low-yield nonspecific hydroxylation of l-Phe by BH 4 in the absence of enzyme occurs without an NIH shift.…”
Section: Introductionmentioning
confidence: 99%
“…Other enzymes for which such an intermediate has been invoked (e.g., iso-penicillin synthase and the α-ketoglutarate dependent hydroxylases) are capable of aliphatic hydroxylation (77). Consistent with such an expectation, all three hydroxylases have been shown to catalyze benzylic hydroxylation of methylated aromatic amino acids (54,85,88). In addition, PheH has been reported to catalyze aliphatic hydroxylation (21,46) and epoxidation (23).…”
Section: Methodsmentioning
confidence: 82%
“…In contrast to the situation with PheH and TyrH, the rate-limiting step in TrpH turnover is oxygen addition to the aromatic ring of the substrate (54). In the hydroxylation of tryptophan, the NIH shift is from C5 to C4 only (58).…”
Section: Methodsmentioning
confidence: 99%
“…For example, experiments suggest that the nitrogen of the indole could play an important role for the appropriate positioning of the amino acid through an essential hydrogen bonding. [46] Experiments indicate an inverse secondary kinetic isotope effect of 0.93 with 5-2 H-tryptophan, but no inverse isotope effect with 4-2 H-tryptophan (the measured isotope effect was in this case 1.03). [11] It was thus suggested that the isotope effect could be ascribed to the CÀO bond formation during the substrate hydroxylation, which in turn has to involve a higher barrier than the one of the cofactor hydroxylation.…”
mentioning
confidence: 78%